The K-Net Development Process: A Model for First Nations Broadband Community Networks - Fiser, Adam; Clement, Andrew; Walmark, Brian (Canadian Research Alliance for Community Innovation and Networking, 2006)
Based on a paper originally prepared for and presented at the Telecommunications Policy Research Conference (TPRC) September 23 to 25, 2005, held at George Mason University School of Law in Arlington, Va. The Kuh-ke-nah Network (K-Net) is a community network that currently comprises 60 First Nations communities across Ontario, and Quebec, Canada. K-Net Services is the telecom and ICT arm of Keewaytinook Okimakanak Tribal Council (the Northern Chiefs), an organization located in northwestern Ontario that brought the original vision of K-Net to life amongst the Tribal Council’s six member communities in the mid 1990’s. This paper traces the evolutionary trajectory of K-Net development and examines the advantages and drawbacks to the emerging model of telecom service provision in which K-Net is a pioneering exemplar. First, it chronologically charts the expanding set of relationships among the heterogeneous key actors across the public, private and civil sectors. Then it reviews the contemporary situation of K-Net, how the combination of such vital factors as community ownership/control, bandwidth aggregation and dynamic allocation, local (ICT) skills development, and social-needs orientation interact with each other and are operationalized within this network of relations. Finally, the paper draws some preliminary conclusions about the principles and viability of this model, likely future development, and the prospect that it offers a workable model for other community networking initiatives, especially in traditionally underserved areas. Social Science and Humanities Research Council (SSHRC) - Initiative on the New Economy Public Outreach Grant; Canadian Research Alliance for Community Innovation and Networking (CRACIN).